1968
DOI: 10.1111/j.1476-5381.1968.tb00436.x
|View full text |Cite
|
Sign up to set email alerts
|

THE OCCURRENCE OF PROSTAGLANDIN E2 IN SPLENIC VENOUS BLOOD OF THE DOG FOLLOWING SPLENIC NERVE STIMULATION

Abstract: Prostaglandins are released when the sympathetic nerves supplying the rat epididymal fat pad in vitro are stimulated (Shaw, 1966). It is not yet known whether this is a general phenomenon associated with adrenergic nerve stimulation but the experiments described in this paper show that prostaglandin E2 is released when the splenic nerve is stimulated. A preliminary account of this work has already been published (Davies, Horton & Withrington, 1967).In the investigation reported here we collected venous blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
1

Year Published

1971
1971
1989
1989

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(66 citation statements)
references
References 9 publications
(9 reference statements)
1
64
1
Order By: Relevance
“…The work of Ramwell et al (1965) with the phrenic nerve diaphragm preparation has already been quoted; more recently the same group have demonstrated release of prostaglandins from adrenals stimulated with acetylcholine (Ramwell, Shaw, Douglas & Poisner, 1966). Davies, Horton & Withrington (1966) have shown that electrical stimulation of splenic nerve leads to release of prostaglandins into splenic venous blood, and Shaw (1966) has found a release of prostaglandins from adipose tissue in vitro in response to sympathetic nerve stimulation. These findings and our own work do not link prostaglandins with any particular component of the nervous system, as the substances may be found in the central and peripheral nervous system, including sympathetic and parasympathetic.…”
Section: Resultsmentioning
confidence: 99%
“…The work of Ramwell et al (1965) with the phrenic nerve diaphragm preparation has already been quoted; more recently the same group have demonstrated release of prostaglandins from adrenals stimulated with acetylcholine (Ramwell, Shaw, Douglas & Poisner, 1966). Davies, Horton & Withrington (1966) have shown that electrical stimulation of splenic nerve leads to release of prostaglandins into splenic venous blood, and Shaw (1966) has found a release of prostaglandins from adipose tissue in vitro in response to sympathetic nerve stimulation. These findings and our own work do not link prostaglandins with any particular component of the nervous system, as the substances may be found in the central and peripheral nervous system, including sympathetic and parasympathetic.…”
Section: Resultsmentioning
confidence: 99%
“…However, phenoxybenzamine abolished the release by adrenaline but not that by bradykinin. We have not attempted to characterize further the prostaglandin(s) released, but in other dog and cat spleen perfusions the release was predominantly of prostaglandin E2 (Davies, Horton & Withrington, 1968;Gilmore et al, 1968;Ferreira, Moncada & Vane, 1973). Bradykinin also causes release of prostaglandin E2 from dog kidney (McGiff, Terragno, Malik & Lonigro, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…In previous experiments on the release of prostaglandins from different tissues in response to a variety of stimuli it was shown that the amounts released within a short period were far in excess of those present in the unstimulated tissues. This suggested rapid synthesis (Ramwell, Shaw, Douglas & Poisner, 1966; Davies, Horton & Withrington, 1968). In fact, as expressed by Piper & Vane (1971) prostaglandin release can often be equated with prostaglandin synthesis.…”
Section: Introductionmentioning
confidence: 99%